El hegelianismo y Kierkegaard (2021)
This essay is aimed at understanding, briefly, the relationship between Hegelianism and Kierkegaard through the intellectual context of Denmark in the first half of the nineteenth century. For this approach it is necessary, in the first place, to verify under what forms German Hegelianism bursts onto the intellectual circles of Copenhagen; then, to probe the existing relationship between this Hegelianism and the figures that give form and content to Danish Hegelianism; and finally, to understand what kind of relationship Søren Kierkegaard maintained with Hegelianism.